PELATIHAN DIVERSIFIKASI PRODUK LIMBAH KELAPA DAN PENGEMASAN MINYAK MANDAR DI KABUPATEN POLEWALI MANDAR - Sanjaya, Muhammad Fahyu; Isdaryanti, Isdaryanti; Kurniawan, Alexander; Maskur, Maskur; Zulkifli, Zulkifli; Saldi, Saldi; Arpin, Arpin; Arpan, Arpan (Jurnal Abdi Insani, 2025)
Coconut waste has significant potential to be developed into value-added products through diversification. Polewali Mandar Regency, known for its coconut and traditional Mandar oil production, faces challenges in the optimal utilization of coconut waste and in scaling up sales of Mandar oil through improved packaging techniques. This training aims to enhance the knowledge and skills of the community in utilizing the abundant coconut resources and improving the quality and marketability of products through better packaging techniques. The methods employed include lectures, demonstrations, discussions, and are concluded with evaluations to measure the success of the activities. Evaluation results indicate a significant improvement in the knowledge and skills of community partners. The material presented during the service program was well-received by the partners, and they were highly interactive, as evidenced by the numerous questions raised during the discussion session, leading to a two-way dialogue. Providing equipment support to the partners has positively impacted their enthusiasm to develop their businesses further, enhancing product quality that is competitive with other coconut-based products. Thus, the implementation of coconut waste product diversification and the improvement of Mandar oil packaging techniques in Polewali Mandar holds potential as a solution to improve the economic welfare of the local community.